Democracy, Geography and Model Uncertainty. (13th October 2017) - Oberdabernig, Doris A.; Humer, Stefan; Crespo Cuaresma, Jesus
Abstract: We analyse the nature of robust determinants of differences in democracy levels across countries taking explicitly into account uncertainty in the choice of covariates and spatial spillovers. We make use of recent developments in Bayesian model averaging to assess the effect of a large number of potential factors affecting democratisation processes and account for several specifications of spatial linkages. Our results indicate that spatial spillovers are present in the data even after controlling for a large number of geographical covariates. Addressing the determinants of democracy without modelling such spillovers may lead to flawed inference about the nature of the determinants of democratisation processes. In particular, our results emphasise the role played by Muslim religion, population size, trade volumes, English language, natural resource rents, GDP per capita, being a MENA country and the incidence of armed conflicts as factors affecting democracy robustly.